The Influence of Environmental, Social, and Governance on Dividend Payouts in Banking Sector Companies in Indonesia - Romadino; Adib Sayubi Nur; Richy Wijaya W (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to gain insight into the influence of environmental, social, and governance on dividend payout, assuming that the environmental, social, and governance factors of an organization are the most important criteria that drive dividend payout. The data used in this study are secondary data sourced from the annual reports of banks listed on the Indonesia Stock Exchange (IDX) from 2023 - 2024. The research sample consists of 17 banks with a total of 34 data that met the criteria. This study uses multiple linear regression analysis on panel data to evaluate the relationship between independent and dependent variables using E-Views 9 software. The results of this study indicate that Environmental Social and Governance Performance (ESG) is not significant to Dividend Payout, Leverage is significantly positive to Dividend Payout, Cash Ratio is significantly negative to Dividend Payout, and Return On Asset is significantly positive to Dividend Payout. The implications of this research can be useful for managers to evaluate performance and financial strategies that affect Dividend Payout and also for investors to consider external factors such as economic conditions. Keywords : Environmental Social and Governance Performance, Leverage, Cash Ratio, Return On Asset, Dividend Payout, Indonesia Stock Exchange.